Nominal Word Order Typology in Signed Languages - Coons, Caitie (Frontiers in Communication, 2022)
Although spoken language nominal typology has been subject to much scrutiny, research on signed language nominal word order typology is still a burgeoning field. Yet, the structure of signed languages has important implications for the understanding of language as a human faculty, in addition to the types of universals that may exist across the world’s languages and the influence of language modality on linguistic structure. This study examines the order of nouns and attributive modifiers (adjectives, numerals, demonstratives, quantifiers, genitives, and relative clauses) in 41 signed languages, which span national and village signed languages from various lineages and geographic regions. Despite previous typological research on clausal phenomena indicating that the clausal structure of signed languages differs systematically from spoken languages (Napoli and Sutton-Spence, 2014, among others), the results of this survey indicate that signed language nominal word order typology is strikingly similar to spoken languages in several ways: (i) the most common word orders in spoken languages are also common in signed languages, (ii) the uncommon word orders in spoken languages are also uncommon in signed languages, but are attested, unlike uncommon major constituent orders, and (iii) the relative ranking of word order strategies, particularly relative clauses, is similar across signed and spoken languages.